QUEUE SYSTEM ANALYSIS TO IMPROVE THE EFFECTIVENESS OF PATIENT SERVICES AT PUSKESMAS PANJANG BANDAR LAMPUNG - Andreas Hutapea; Defrizal Defrizal (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This study aims  to analyze queue design and improve the effectiveness of services to patients at Puskesmas Panjang Bandar Lampung. The research model used is a descriptive quantitative method using an observation model. The analysis tool applied is M/M/S, and this research was carried out at the Long Health Center Bandar Lampung. The study sample was taken through observation time at the location, while the population that was the focus was patient service at the registration counter of Puskesmas Panjang Bandar Lampung. The type of data needed includes primary and secondary data, obtained through observation, interviews with officers of the Bandar Lampung Long Health Center, and secondary data based on the biography of the Puskesmas. The results showed that the queuing design applied at the Bandar Lampung Long Health Center Registration Counter was a Multi-Channel-Single Phase queue system. The performance of the queuing system at the Bandar Lampung Long Health Center counter has reached an optimal level based on the evaluation results of the analyzed indicators.